Analisis Kepatuhan dan Optimalisasi Perhitungan serta Pelaporan PPh Pasal 23 pada PT XYZ - Devi, Ameylia Shintya; Sucahyati, Diarany (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
Income Tax (PPh) Article 23 is an essential component of Indonesia’s taxation system. It is levied on income received by domestic taxpayers from capital, services, or awards. This study aims to evaluate the calculation and reporting of PPh Article 23 at PT XYZ, identify underlying issues, and propose solutions to enhance compliance and reporting efficiency. The research adopts a descriptive qualitative method through a case study approach. Data were collected via direct observation of the company’s tax administration process, interviews with the finance department, and a review of supporting tax documents. The findings reveal discrepancies between reported amounts and actual tax payment dates, which may expose the company to administrative sanctions. The study highlights the need for PT XYZ to strengthen its understanding of PPh Article 23 regulations, optimize the use of the Directorate General of Taxes’ digital platform (Coretax), and improve internal procedures through the implementation of clear Standard Operating Procedures (SOPs) and staff training. These steps are crucial to prevent future errors and ensure sustainable tax compliance. This research is expected to serve as a strategic reference for PT XYZ in managing tax obligations more effectively and aligning with prevailing tax laws.